Stock Prices, Earnings, and Expected Dividends - CAMPBELL, JOHN Y.; SHILLER, ROBERT J. (Journal of Finance, 1988)
ABSTRACT Long historical averages of real earnings help forecast present values of future real dividends. With aggregate U.S. stock market data (1871–1986), a vector‐autoregressive forecast of the present value of future dividends is, for each year, roughly a weighted average of moving‐average earnings and current real price, with between two thirds and three fourths of the weight on the earnings measure. We develop the implications of this for the present‐value model of stock prices and for recent results that long‐horizon stock returns are highly forecastable.